Environmental awareness in rural Bangladesh: levels and differentials - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
This report assesses the level of environmental awareness in the rural communities of Bangladesh. Findings reveal that nearly half of the people were aware about the change of environment and its implications although the knowledge about the specific aspects of environmental change is poor. Regional as well as socioeconomic differentials in environmental awareness were very high. NGOs played an important role in raising the awareness level. The study suggests that a concerted effort should be initiated including both the public and private development organizations to routinely disseminate the consequences of environmental disaster.